Theory of nonequilibrium transient transport in nanostructures. (22nd August 2008) - Maciejko, Joseph; Zhu, Yu; Wang, Jian; Guo, Hong
We present a brief review of time dependent quantum transport theory for analysing nanoelectronic devices. We focus on both theoretical and numerical techniques developed recently for calculating time-dependent current flowing through noninteracting phase-coherent conductors connected to external leads, in response to external time dependent bias voltages. For sharp step- and square-shaped voltage pulses, we report an exact analytical theory based on the Keldysh nonequilibrium Green's functions (NEGF), for solving the transport equations in the far from equilibrium, nonlinear response regime. We also report a numerical approach based on NEGF and the time-domain decomposition scheme. The essential feature of our theory is that it does not rely on the commonly used wideband approximation, as such they provide a way to perform practical transient transport calculations from first principles on realistic devices.